Atmospheric circulation patterns associated with extreme precipitation events in Eastern Siberia and Mongolia - Antokhina, Olga Yu; Antokhin, Pavel N.; Gochakov, Alexander V.; Zbirannik, Anna; Gazimov, Timur (Atmosphere)
Abstract: The socioeconomic impacts caused by floods in the south of Eastern Siberia (SES), and the expected increase in precipitation extremes over northern Eurasia, have revealed the need to search for atmospheric circulation patterns that cause extreme precipitation events (EPE) in SES, as well as their changes. We investigate the circulation patterns causing extreme precipitation in SES and Mongolia, by examining the instability and moisture transport associated with potential vorticity (PV) dynamics during two time periods: 1982-1998 and 1999-2019. The EPE were characterized by an increase in instability within the precipitation area, which was compensated by stability around the area, with the East Asian summer monsoon transport being enhanced. PV in the subtropical regions and mid-latitudes has shown the amplification of positive and negative PV anomalies to the southeast and northwest of Lake Baikal, respectively. The PV contours for EPE have shapes of cyclonic wave breaking and cutoff low. EPE accompanied by wave breaking are characterized by strong redistribution areas, with extremely high and low stability and moisture. This can lead to the coexistence of floods and droughts, and in part was the driver of the earlier revealed "seesaw" precipitation mode over Mongolia and SES. We suggest a shift of extreme precipitation to the northwest has occurred, which was probably caused by the wave propagation change.